Pension Sector Reforms in India Rationale, Concept and Issues - Chauhan , Mukesh (Gyan Management Journal, 2008)
In all the dev lop d and developing country their join L family are conv rted in to nuclear family and more or less after retirement all the employees ar dire tly d pends upon their childr n’s for their old ages curity. nother reason is due to bett r medical facilities life expectancy are increase radually and again question f social security is increasing . The decline rate of joint families particularly in urban areas is of concern of both the societies I it creates major issues pertaining to old ag s curity. Similarly th traditional and informal m lhod of old ag in ome, ecurity ar not able to cop with th trends of increased life pan and enhancem nt of medical expense during the old age, h nee its very important to reexamine the existing formal and informal ystem of social s curity.